Peran Kepala Sekolah Sebagai Motivator Dalam Meningkatkan Disiplin Kerja Guru - Yuliarti , Nuryeni; Nur Sasongko , Rambat (UNIVERSITAS BENGKULU, 2023)
The aim of this study was to describe the principal’s role as motivator in improving discipline work teacher’s, method use descriptive qualitative, data collecting technique use interview, observation, documentation. Data analysis technique used interactive Huberman, that shows, 1) improving timeliness principal apply android presensi and gave a snack to teacher who come early, 2) improving adherence standard work preparation learning tools principal perform in house training and supervisi, 3) improving adherence discipline teacher, principal sets a great for example star discipline from herself, give advice to obey rules, 4) proponent discipline factor work teacher principal make herself as example, reward, spirit, punishment, maintain good relations with teacher.